MODULATING EFFECT OF CARVEDILOL ON ACTIVATION OF CYTOKINES IN PATIENTS WITH CHRONIC HEART FAILURE CAUSED BY ARTERIAL HYPERTENSION - Imamaliyev, G.M.; Nuriyev, A.A.; Gurbanova, Kh.I.; Amrahova, L.G.; Alikhanova, I.Ch.; Bayramova, S.A.; Aliyeva, S.A. (World of Medicine and Biology, 2025)
To assess the 6-month treatment with carvedilol, depending on the levels of proinflammatory cytokines (interleukin-1, interleukin-6 and tumor necrosis factor-α) in patients with arterial hypertension associated with chronic heart failure. The observation and treatment were conducted in 43 patients (mean age 51.3±3.2 years). The patients were divided in two groups. In patients of the 1st group with chronic heart failure of the II class according to New York Heart Association (n=22), the blood content of proinflammatory cytokines (p